On the solutions of linear ordinary differential equations and Bessel-type special functions on the Levi-Civita field - A. R. Mészáros; Kh. Shamseddine (Հայաստանի ԳԱԱ)
Becouse of the disconnectedness of a non-Archimedean ordered field in the topology induced by the order, it is possible to have non-constant fuctions with zero derivatives everywhere.
Keywords: Geometry; Trigonometry; Topology; Mathematics; Science